Answers

2015-10-18T09:38:13+05:30
x-2=0
x=2 (factor of the polynomial)
x+1/2=0
x=-1/2 (factor of the polynomial)

x-2 as a factor,
px^2+4(2)+r= 0
⇒4p+8+r=0 ----------------------------(1)
now, x=+1/2 as a factor
p(-1/2)^2+4( -1/2)+r=0.
1/4p-4/2=0 --------------------------(2)

from the equation (1) and (2)
4p+8+r=1/4p-4/2+r=0
⇒4p-1/4p=-4/2-8+r-r
⇒(16p-1p)/4=-20/2
⇒15p/4=-10
⇒15p=-10*4
⇒15p=40
⇒p=40/15
⇒p=8/3
∴in the equation 3p+16=3r
⇒ 3(8/3)+16=3r    
⇒ 8+16=3r
⇒24=3r
⇒24/3=r
⇒8=r
∴by putting the value of p and r in the given equation ,
we get,
3p+16=3r.
3(8/3)+16=3(8)
8+16=24
24=24
∴R.H.S=L.H.S
hence proved.
      i hope that it will help u...............





0